1988
DOI: 10.1021/ic00286a024
|View full text |Cite
|
Sign up to set email alerts
|

Hexanuclear iron-sulfur basket clusters: topological isomers of prismanes. Synthesis, structure, and reactions

Abstract: Thus neither e" nor ew for CN" can be even approximated from this treatment. It is also unrealistic to accept the best-fit f values, even when the propagated error turns out to be small, because changes in f induce smaller changes in the transition energies than would such factors as the inclusion of additional K+ (or [Cr-(CN)6]3~) ions in the model.The value of the Trees parameter, 211 cm™1 using the Pean structure, appears large by comparison with the 70-cm™1 value for the free Cr3+ ion.8 Smaller values of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…In terms of just carbide coordination, no molecular entity comes closer than [Fe 6 C(CO) 16 ] 2−234 in which a carbon atom resides at the center of an Fe 6 octahedron at 1.88−1.91 Å, 235 but the formal (29) and supported by an idealized synthetic Cys-containing helical peptide (34). Discrete covalently bridged synthetic clusters (35,36) are perhaps plausible; however, 35 (X = HS − ) and 36 have not been prepared. iron oxidation state is completely unrealistic for a protein site.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of just carbide coordination, no molecular entity comes closer than [Fe 6 C(CO) 16 ] 2−234 in which a carbon atom resides at the center of an Fe 6 octahedron at 1.88−1.91 Å, 235 but the formal (29) and supported by an idealized synthetic Cys-containing helical peptide (34). Discrete covalently bridged synthetic clusters (35,36) are perhaps plausible; however, 35 (X = HS − ) and 36 have not been prepared. iron oxidation state is completely unrealistic for a protein site.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…[Fe 8 S 8 ] 0 (12) ↔ [Fe 4 S 4 ] 1+,0 (4) Double cubanes 12 are readily cleaved by excess carbene in reactions (32) (63%) and (33) (nearly quantitative) or with a variety of other ligands in the presence of a suitable oxidant to afford the cubane clusters 4 in the all-ferrous or one-electron oxidized state (20−50%). Reactions (32)−(35) are further examples of double to single cubane conversions leading to 4 in two different oxidation states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are of course some exceptions, including among others [Fe 4 S 4 (STip) 2 {SC(NMe 2 ) 2 } 2 ] prepared in toluene 140 and, more recently, [Fe 4 S 4 {N(SiMe 3 ) 2 } 4 ] ( 13 , Figure 3) also prepared in toluene. Octanuclear [Fe 8 S 12 (RNC) 12 ] clusters have been synthesized in benzene from the fragment coupling reaction of [Fe 4 S 4 (SEt) 2 (RNC) 6 ] and (PhCH 2 S) 2 S. 141 Certain neutral clusters such as [Fe 6 S 6 (PEt 3 ) 4 X 2 ] 116,142 (X = halide, PhS − ), [Fe 7 S 6 (PEt 3 ) 4 Cl 3 ], 143 and [Fe 8 S 8 (Pr i 2 NHCMe 2 ) 6 ( 12 , Figure 3) are pr143epared in THF whose dielectric constant (ε 7.52) is somewhat higher than that of toluene (ε 2.38).…”
Section: Fe8s7 Clusters By Non-polar Assemblymentioning
confidence: 99%
“…The biological significance of the oxidative disassembly of the [Fe 4 S 4 ] cluster draws attention to the molecular basis of this reaction. As fundamental knowledge for iron–sulfur clusters, the conversion of [Fe 4 S 4 ] cluster into [Fe 2 S 2 ] clusters is highly attractive but remains unprecedented, and notably, little has been known about transformations of synthetic [Fe 4 S 4 ] clusters. , Recently, we have demonstrated that the highly oxidized all-ferric [Fe 4 S 4 ] cluster Fe 4 S 4 {N­(SiMe 3 ) 2 } 4 ( 1 ) , can be transformed into [Fe 8 S 7 ] clusters representing the core of a nitrogenase P-cluster, through the reductive desulfurization of the cubic core induced by phosphines . This result prompted us to explore core transformations of all-ferric [Fe 4 S 4 ] cluster 1 , and herein we report our discovery of a novel transformation of an [Fe 4 S 4 ] core from cluster 1 into two [Fe 2 S 2 ] clusters in the presence of pyridines.…”
Section: Introductionmentioning
confidence: 99%